Investigating The Influencing Factors Of Consumers' Museum Cultural And Creative Product Purchase Intention In China - Ding, Lilan (2024)
The purpose of this study is to identify and analyse the determinants influencing Chinese consumers' intentions to purchase Museum Cultural and Creative Products (MCCPs). Employing the Stimulus-Organism-Response (SOR) theoretical framework, the research examines multidimensional product factors—including perceived entertainment, quality, and cultural attributes—and socio-environmental factors such as subjective norms. These variables are studied in relation to purchase intention through the mediating effects of perceived value and attitudes towards MCCPs. Quantitative research methods were utilized, with data collected through surveys and subsequently analysed using SPSS 25.0 and AMOS 26.0. The findings indicate that internal mental state factors, such as perceived value, perceived behaviours control, and attitude, significantly enhance consumers' purchase intention. Furthermore, multidimensional product factors increase purchase intention via perceived value, and attitudes influence purchase intention through socio-environmental factors. Notably, perceived entertainment did not mediate the relationship between perceived value and purchase intention.